Contribuição ao conhecimento fitoquímico de Cissampelos sympodialis Eichl. (Menispermaceae) - Lima, Natanael Teles Ramos de (2020)
Cissampelos sympodialis Eichl., popularly known as “milona”, “jarrinha”, “abuteira” and “orelha-de-onça”, it is a species rich in alkaloids and has traditional use in the treatment of asthma, bronchitis, rheumatism and arthritis. Thus, the objective of this work was to contribute to the chemical and pharmacological knowledge of the species, through the isolation of substances, mass spectrometry, in silico studies and biological tests. The aerial parts were collected in the garden of UFPB’s Research Institute for Drugs and Medicines – IpeFarM and an exsiccate is deposited in the Herbarium Prof. Lauro Pires Xavier under AGRA 1476 registration and in the National System of Management of Genetic Heritage and Associated Traditional Knowledge (SisGen) under the code A9B2EFC. After harvest, drying and grinding, extraction was performed with 95% ethanol and then the solvent was concentrated in a rotary evaporator, obtaining the Crude Ethanol Extract (CEE). The CEE was partitioned using hexane, chloroform and ethyl acetate. The hydromethanolic phase was subjected to open column chromatography using Sephadex-LH 20, resulting in the CsFHM 6-7 fraction that was processed by preparative High Performance Liquid Chromatography (HPLC). An alkaloids march was performed to obtain the Alkaloid Rich Fraction (ARF). The isolated compounds were identified using Mass spectrometry (MS), Nuclear Magnetic Resonance (NMR) and comparison with the literature. A molecular docking study was carried out on alkaloids already isolated from milona: laurifolin, milonine, warifteina, methylwarifteina, roraimina, des-7'-O-methylroraimina and epi-des-7'-Omethylroraimina; to evaluate their interactions with Topoisomerase IIα and DNA. An MTT assay was performed with samples of C. sympodialis in breast cancer cells, human melanoma, colon carcinoma, cervical adenocarcinoma and in normal human keratinocyte cells. The preparative HPLC allowed the isolation of 4 substances: the nucleoside adenosine and three flavonoids, vicenin-2, quercetin-3-O-βglycopyranosyl-(1→6)-β-galactopyranoside and canferol-3-O-β-glycopyranosyl- (1→6)-β-galactopyranoside. In addition, from the literature, 10 more compounds were identified by LC-MS: caffeic acid-hexoside, salsolinol, guanosine, syringic acid-Ohexoside, magnoflorin, benzyl alcohol-hexose-pentose, aromadendrine-hexoside, apigenin-6-C-glycoside, isoquercetin and astragalin. The docking pointed out that among milona alkaloids, roraimine is the one that best interacts with Toposiomerase IIα and with DNA and des-7'-O-methylroraimine is the best as a DNA ligand. The MTT assay indicated that CEE has inhibitory activity in colon and breast cancer cells and ARF was able to strongly inhibit the growth of all tested strains, although it has an action against normal cells. The test also demonstrated that the glycosylated flavonoids have no activity against the tested cell lines. It is concluded that milona has potential antitumor activity and that it can eventually be used as a complement in the treatment of cancer, in addition to theoretically having chemical compounds that can become active drugs against neoplasms.